Nitsiyihkâson: The Brain Science behind Cree Teachings of Early Childhood Attachment - Pazderka, Hannah; Desjarlais, Brenda; Makokis, Leona; MacArthur, Carly; Steinhauer, Sharon; Hapchyn, Carole; Hanson, Tara; Van Kuppeveld, Nicole; Bodor, Ralph (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2014)
The Nitsiyihkâson project was conceived in order to develop a resource to promote attachment and development in a manner culturally appropriate to the Indigenous (specifically Cree) people of Alberta. Promoting secure attachment between a child and his/her caregivers is crucial to ensuring positive mental health, and improving family well-being. Working collaboratively with the community of Saddle Lake, the process began by launching the project in traditional ceremony. Following this, a talking circle was held with Saddle Lake Elders to share their memories and understanding of child-rearing practices that promote attachment. Using their guidance, we produced the document “awina kiyanaw”, which focuses on Cree stories and teachings, for parents to share with their young children. This document will be shared within the community, and agencies interested in promoting a culturally-appropriate approach to parenting. We then examined the cross-cultural applicability of these practices and produced a Resource Manual for service providers, comparing traditional ways-of-knowing with current neurobiological and epigenetic scientific understanding. We believe this helps those working with Indigenous families better understand their culture, and appreciate the wisdom in its teachings. In this paper, we present those findings and their ramifications.